2017
DOI: 10.1007/978-3-319-61845-6_38
|View full text |Cite
|
Sign up to set email alerts
|

Post-marketing Drug Safety Evaluation Using Data Mining Based on FAERS

Abstract: Healthcare is going through a big data revolution. The amount of data generated by healthcare is expected to increase significantly in the coming years. Therefore, efficient and effective data processing methods are required to transform data into information. In addition, applying statistical analysis can transform the information into useful knowledge. We developed a data mining method that can uncover new knowledge in this enormous field for clinical decision making while generating scientific methods and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…9 We have previously investigated this database to explore the feasibility of using FAERS to analyze mental health drug safety using 12 first-line antidepressants drugs. 10 We found that our results were qualitatively in agreement with results from the recent comprehensive systematic review of randomized controlled trials. 5 Moreover, our postmarketing analysis based on FAERS provided more insight into different types of adverse reactions with respect to different classes of human organ system and a larger population.…”
Section: Introductionsupporting
confidence: 90%
“…9 We have previously investigated this database to explore the feasibility of using FAERS to analyze mental health drug safety using 12 first-line antidepressants drugs. 10 We found that our results were qualitatively in agreement with results from the recent comprehensive systematic review of randomized controlled trials. 5 Moreover, our postmarketing analysis based on FAERS provided more insight into different types of adverse reactions with respect to different classes of human organ system and a larger population.…”
Section: Introductionsupporting
confidence: 90%
“…The U.S. Food and Drug Administration (FDA) adverse event reporting system (FAERS) provides information on medication error reports and adverse events (AEs). Data mining algorithms are routinely applied for the quantitative detection of signals, such as drug-associated AEs ( 8 ). Therefore, we aim to assess the potential relevance between ACEIs and primary malignant lung cancer AE reports through data mining of the FAERS.…”
Section: Introductionmentioning
confidence: 99%